2018
DOI: 10.1002/jac5.1051
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of systematic anticoagulation management in pharmacist and nurse specialized clinics

Abstract: Background While systematic anticoagulation management leads to improved outcomes, there is limited data comparing outcomes in anticoagulation clinics managed by pharmacists vs nurses. The objective of this study was to evaluate the effect of pharmacist vs nurse‐managed clinics on the quality of anticoagulation and warfarin‐related hospitalizations and emergency department (ED) admissions. Methods A retrospective observational cohort study of patients treated with warfarin and referred to a pharmacist‐managed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…Manzoor and colleagues did not note a difference in anticoagulation control between the pharmacist and the nurse AMS model. However, patients in the pharmacist AMS had a comparatively lower odds of experiencing a hospitalization or emergency department visit, leading to a cost avoidance of nearly $5000 per patient over 1.25 years . In combination, these studies further demonstrate that pharmacist AMS result in an improvement in quality outcomes and a reduction in health care utilization over other models.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…Manzoor and colleagues did not note a difference in anticoagulation control between the pharmacist and the nurse AMS model. However, patients in the pharmacist AMS had a comparatively lower odds of experiencing a hospitalization or emergency department visit, leading to a cost avoidance of nearly $5000 per patient over 1.25 years . In combination, these studies further demonstrate that pharmacist AMS result in an improvement in quality outcomes and a reduction in health care utilization over other models.…”
mentioning
confidence: 77%
“…In this issue of the Journal of the American College of Clinical Pharmacy, there are two studies evaluating warfarin management in pharmacist-run AMS compared with nurse-run models. 5,6 Tarasiuk and colleagues found that fewer all-cause hospitalizations occurred with pharmacist-vs nurse-managed AMS. 5 Patients in the pharmacist AMS also had a significantly higher measure of anticoagulation control compared with those in the nurse AMS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This issue of JACCP contains several papers demonstrating that pharmacists impact and improve patient care. Compared to nurse‐managed programs, pharmacist‐managed anticoagulation services were associated with reduced hospitalization rates in two studies, decreasing costs by more than $500 000 at one institution . In patients with acute coronary syndrome, inclusion of pharmacists in both shared decision‐making for the selection of antiplatelet therapy and transitions of care were associated with a high frequency of patient‐centered interventions and lower rates of rehospitalization …”
mentioning
confidence: 99%
“…Compared to nurse-managed programs, pharmacistmanaged anticoagulation services were associated with reduced hospitalization rates in two studies, decreasing costs by more than $500 000 at one institution. 8,9 In patients with acute coronary syndrome, inclusion of pharmacists in both shared decision-making for the selection of antiplatelet therapy and transitions of care were associated with a high frequency of patient-centered interventions 10 and lower rates of rehospitalization. 11 Given the dynamic nature of health care today and the fragile financial status of many medical centers, the profession of pharmacy, in general, and cardiology clinical pharmacy specialists, in particular, need to work together to continue to produce high-quality evidence demonstrating our value regarding clinical, economic, and humanistic outcomes.…”
mentioning
confidence: 99%